2021
DOI: 10.3390/math9080822
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Measures and Profit Exploration of Windmill Water-Pumping Systems Incorporating Warranty and Two Types of Repair

Abstract: Wind energy is a kind of renewable energy that plays a significant role in remote areas for pumping water. The windmill is also used to generate electricity. The windmill is also known as a wind pump when it is used for pumping water. In this work, the authors proposed a complex hybrid model of an example of combined system (windmill, rechargeable battery and pumping system) to evaluate the system’s performance. System performance was affected by system degradation due to system failure. These factors also aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Okamura and Dohi (2021) explored the applicability of evolutionary algorithms in the reliability evaluation of complex systems. Goyal et al (2021) suggested a stochastic model for a water pump used in windmills using the concept of warranty. D'Amico et al (2021) developed some semi-Markov reliability models for the computation of some interval reliability indicators.…”
Section: Optimization Of Biological and Chemical Unitmentioning
confidence: 99%
See 1 more Smart Citation
“…Okamura and Dohi (2021) explored the applicability of evolutionary algorithms in the reliability evaluation of complex systems. Goyal et al (2021) suggested a stochastic model for a water pump used in windmills using the concept of warranty. D'Amico et al (2021) developed some semi-Markov reliability models for the computation of some interval reliability indicators.…”
Section: Optimization Of Biological and Chemical Unitmentioning
confidence: 99%
“…Okamura and Dohi (2021) explored the applicability of evolutionary algorithms in the reliability evaluation of complex systems. Goyal et al. (2021) suggested a stochastic model for a water pump used in windmills using the concept of warranty.…”
Section: Introductionmentioning
confidence: 99%
“…The semianalytical pump model based on interpolation of catalogue data at the rated rotational speed is commonly used for pumping system analysis [15,33]. When analyzing pumping systems, methods of multicriteria optimization [34,35], statistical methods of reliability analysis [36], and neural networks [37] are also often used.…”
Section: Literature Review and Novelty Of The Studymentioning
confidence: 99%